Effect of cascade STATCOM on stabilising voltage in high voltage direct current. Issue 16 (23rd November 2018) - Jiaqi, Li; Jun, Wen; Helin, Liu; Shiyou, Yu
Abstract : Yongfu high voltage direct current (HVDC) project in Yunnan is the main access to send the power out and also an important part of the channel of transmission of power in west to east in China southern power grid. However, the Funing Converter Station of the project connects to a weak AC system; thus, there is a need for a Static Synchronous Compensator (STATCOM) to compensate the reactive power. This study presents the principle of the STATCOM, all kinds of the topologies of STATCOM, with their advantages and disadvantages compared to each other and the representative projects. Then, the cascade STATCOM is emphatically analysed that is applied to the project. Also, the cascade STATCOM model and the project model are established in PSCAD/EMTDC. Afterwards, the effect of STATCOM on the converter station is studied, which works in steady state and in transient of varieties of short circuit faults. Finally, the simulation results verify the effectiveness of cascade STATCOM on stabilising the voltage.